Kepastian Pemenuhan Hak-Hak Perempuan dan Anak Pasca Perceraian di Indonesia dan Malaysia - Pasla, Jimmi; Akbarizan, Akbarizan (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The study uses a comparative study approach to provide knowledge and information related to the certainty of the fulfillment of women's and children's rights after divorce in Indonesia and Malaysia, in accordance with the provisions stipulated in the laws and regulations of each country. The research method in this study is normative legal research, by analyzing library study materials and supported by other secondary data. The research findings show that the fulfillment of women's and children's rights after divorce in Indonesia is regulated in Law Number 1 of 1974 concerning Marriage and the Kompilasi Hukum Islam (KHI). Several rights are regulated which are the responsibility of the father. The child's right to receive maintenance and education is a manifestation of the parents' obligations, as regulated in Law Number 23 of 2002 concerning Child Protection and Law Number 9 of 1979 concerning Child Welfare. The amount of maintenance to be paid is determined by the Court. If the Court considers that the father is considered incapable, then the responsibility for the costs also shifts to the mother. In Malaysia, there are clearer regulations regarding the rights of women and children after divorce. This is seen through the establishment of Bahagian Sokongan Keluarga (BSK), a division that has full authority to handle cases of violations related to these rights. BSK operates as a special department under the Jabatan Kehakiman Syariah Malaysia (JKSM), which is under the auspices of the Jabatan Perdana Menteri (JPM). This institution has the authority to resolve various issues related to the provision of maintenance, in order to ensure justice for those who are entitled to receive it.